2010
DOI: 10.1007/s13105-010-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

A single session of intense exercise improves the inflammatory response in healthy sedentary women

Abstract: Physical activity has a great capacity for modulating the immune system, including the inflammatory response. However, the effects of exercise on the inflammatory response have rarely been studied in women, even though women are more susceptible than men to chronic inflammatory diseases. The aim of this study was to ascertain the effect of single sessions of exercise on the inflammatory response of sedentary women, evaluating neutrophil function and circulating concentrations of inflammatory cytokines. Exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…In contrast to our results, Pereira [13] found that women in better physical conditions presented lower IL-6 and TNF-α concentration and increased IL-10 concentration [13]. Conversely, other studies, including our own, did not find a significant association between physical activity and cytokine in women [11,40]. One possible explanation for the different results regarding gender may be related to hormonal differences that interfere with the inflammatory profile [41] and to the fact that women present physiologically increased fat concentration, which releases a high concentration of pro-inflammatory cytokines [42].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Pereira [13] found that women in better physical conditions presented lower IL-6 and TNF-α concentration and increased IL-10 concentration [13]. Conversely, other studies, including our own, did not find a significant association between physical activity and cytokine in women [11,40]. One possible explanation for the different results regarding gender may be related to hormonal differences that interfere with the inflammatory profile [41] and to the fact that women present physiologically increased fat concentration, which releases a high concentration of pro-inflammatory cytokines [42].…”
Section: Discussioncontrasting
confidence: 99%
“…After 30 min of incubation, the plates were washed, fixed and stained, and the number of particles ingested by 100 neutrophils was determined (Latex Bead Phagocytosis Index) under phase contrast microscopy [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The neutrophils’ oxygen-dependent microbicidal capacity (production of O 2 – ) was evaluated by the Nitroblue Tetrazolium (NBT) Reduction Test [15]. An aliquot of 250 µl of neutrophil suspension (10 6 cells/ml) was incubated for 30 min with an equal volume of NBT (Sigma, 1 mg/ml in PBS solution) in the presence of 20 µl of latex beads (1.09 mm 1% in PBS).…”
Section: Methodsmentioning
confidence: 99%
“…•-has been reported to be increased in the brain (Pedreanez et al, 2006), skeletal muscle (Brooks et al, 2008), peritoneal macrophages (De la Fuente et al, 1995), neutrophils (Garcia et al, 2011) and lymphocytes (Tanimura et al, 2008). Similarly, • NO has been reported to be increased in skeletal muscle (Brooks et al, 2008), CD34…”
Section: Multiple Sources and Tissues Generate Reactive Species Durinmentioning
confidence: 98%